1982
DOI: 10.1007/bf01805718
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of the mammary gland and susceptibility to carcinogenesis

Abstract: It has been demonstrated that in humans certain factors such as early menarche, late pregnancy, and nulliparity are associated with a higher risk of developing breast cancer, while early pregnancy acts as a protective factor. Induction of mammary cancer in rats by administration of the chemical carcinogen 7,12-dimethylbenz(a)anthracene reveals that the same factors influencing human breast cancer risk also affect the susceptibility of the rat mammary gland to the chemical carcinogen. Nulliparous rats and rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
404
1
7

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 563 publications
(426 citation statements)
references
References 240 publications
(200 reference statements)
14
404
1
7
Order By: Relevance
“…With regard to risk factors related to pregnancy, on the basis of a suggested influence of full-term pregnancy on breast cells (Russo et al, 1982), an increase in full-term pregnancies would be expected to correlate with a decreased risk of breast cancer in postmenopausal women (Table 1). However, in our premenopausal women, no notable difference in these protective effects was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to risk factors related to pregnancy, on the basis of a suggested influence of full-term pregnancy on breast cells (Russo et al, 1982), an increase in full-term pregnancies would be expected to correlate with a decreased risk of breast cancer in postmenopausal women (Table 1). However, in our premenopausal women, no notable difference in these protective effects was observed.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental studies on full-term pregnancy in rats are shown to result in permanent differentiation in vulnerable breast stem cells, altering subsequent susceptibility to hormones (Russo et al, 1982). This suggests a decreased risk of breast cancer in women who have their first birth at a younger age or in women who have more full-term pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid multiplication occurs during puberty, diminishing the time available for DNA repair between replications [1]. The anti-oestrogenic properties of cigarette smoke [26] could reduce the proliferation of breast tissue, thus reducing breast density.…”
Section: Main Findings and Interpretationmentioning
confidence: 99%
“…The rapid sequential cell divisions during puberty diminish the time available for DNA repair between replications [1]. The breast cells remain as stem cells until a woman's first pregnancy, when extensive, although not complete, cellular differentiation occurs, thus reducing the pool of multiplying stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies of breast cancer risk suggest that a positive association with smoking may emerge 30 -40 years after commencement (Terry and Rohan, 2002), particularly among chronic heavy smokers. There is also evidence to suggest that smoking prior to a first full-term pregnancy may be an important exposure (Russo et al, 1982;Band et al, 2002;Terry and Rohan, 2002). In addition, an increasing number of studies suggest that a possitive association between smoking and breast cancer risk may be stronger among (or limited to) women with certain genotypes (Terry and Rohan, 2002).…”
mentioning
confidence: 99%